Discourse of Intertextuality in the Language of Political Advertisements in Selected Nigerian Newspapers - Ayokunle, Osakinle Patrick (Elsya : Journal of English Language Studies, 2024)
Though Critical Discourse Analysis (CDA) has been used extensively by scholars of ideological discourse to deconstruct the rhetoric of Nigeria's political leaders and the media's portrayal of power and ideology, it has yet to be applied to the language of Nigeria's political advertisements. While taking into account the rhetorical effects of intertextuality on the masses, this paper investigates the aspect of intertextuality in Critical Discourse Analysis as a discursive strategy projected tactically to reflect power struggle and the ideological assumptions of the authors of the advertisements. This study uses Norman Fairclough’s and Teun van Dijk’s traditions of Critical Discourse Analysis (CDA) and political theories as its theoretical basis. Thirty political advertisements were collected from February and March 2007 issues of The Guardian, The Nation, and The Punch; out of which ten were purposively chosen and analysed for this research. This research analyses the data on the language of political advertising in Nigeria to see how power and ideology are represented via rhetorical strategies in the intertextual connections of language use in Nigerian politics. Therefore, the results of this research show that Nigerian politicians have both overt and covert influence over the electorates by employing manifest intertextuality as a rhetorical mechanism that can alter the meaning or interpretation of discourse/text in the mental model of the masses in order to carry out certain discourse functions, each of which has been found to have distinct ideological implications that the politicians are either unaware of or choose to ignore.